Peternakan Berbasis Pesantren : Optimalisasi SDM dalam Ekosistem Al-Ittifaq - Tri Harjawati; Sarah Athifah; Syifa Marhamah (Sosio-Didaktika: Social Science Education Journal, 2025)
This study aims to understand human resource management (HRM) in the livestock unit of the Al-Ittifaq Islamic Boarding School. This study using a qualitative approach with a case study method. Data was collected through in-depth interviews, observations, and documentation of three sources: managers, active students, and alumni who were selected purposively. The results of the study show that HRM is integrated with the “3 Ur” values (ma'ur, idle land, unemployment) covering five main aspects. First, open recruitment without formal selection based on willingness to learn and readiness to adapt. Second, training is carried out through learning by doing with the assistance of senior students and intergenerational knowledge transfer. Third, a systematic work rotation system from barn maintenance, feeding, waste management, to marketing. Fourth, division of responsibilities through a participatory daily evaluative forum (post-dawn recitation). Fifth, rewards in the form of greater trust and responsibility as well as business capital support, while guidance is educational in nature through the addition of tasks. This practice is effective by applying the “3 Ur” principle, which emphasizes the optimization of time, land, and resources, supported by mentoring based on role models and a spiritual approach. Even without a formal managerial system, this model has proven to be productive and sustainable in shaping the character of students who are skilled, have social-spiritual awareness, and can be a reference for other institutions. Keywords: Human Resource Management, Islamic Boarding School, Livestock Farming, Practical Learning.